The association between dietary fiber intake and pelvic inflammatory disease in women: findings from the NHANES 2015–2018 - Hongyu Jin; Zhaoyuan Niu; Xinyue Zhao (BMC Women's Health)
Abstract Background and aim Pelvic inflammatory disease (PID) is a common and serious gynecological condition caused by ascending infections of the female genital tract. It affects approximately one million women annually in the United States and is a leading cause of infertility, ectopic pregnancy, and chronic pelvic pain. While well-established risk factors include multiple sexual partners and sexually transmitted infections, emerging evidence suggests that dietary factors may also influence systemic and reproductive tract inflammation. In particular, dietary fiber has been shown to exert anti-inflammatory effects and promote a healthy balance of gut and vaginal microbiota. This study aimed to examine the association between dietary fiber intake and the prevalence of PID using nationally representative data from the National Health and Nutrition Examination Survey (NHANES). Methods and results We analyzed data from 2,345 women who participated in the 2015–2018 NHANES cycles. Dietary intake was assessed using two non-consecutive 24-hour dietary recalls based on the USDA’s What We Eat in America (WWEIA) protocol. The first recall was conducted during an in-person household interview, and the second via telephone 3–10 days later. To investigate the relationship between dietary fiber intake and PID, we employed multivariable logistic regression, subgroup analysis, smoothed curve fitting, and threshold effect modeling. In fully adjusted models, each additional 1 g/day of dietary fiber intake was associated with a 5% reduction in the odds of PID. Women in the highest quartile of fiber intake had a 69% lower prevalence of PID compared to those in the lowest quartile. A smoothed curve analysis revealed an L-shaped relationship, with an inflection point at 19.45 g/day. Intake above this threshold was significantly associated with lower PID prevalence. Conclusions Higher dietary fiber intake was associated with a lower prevalence of PID among U.S. women. These findings suggest that increasing dietary fiber consumption may help reduce the risk of PID and improve reproductive health outcomes.